2010
DOI: 10.1111/j.1525-1470.2009.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Trials Supporting Benzyl Alcohol Lotion 5% (UlesfiaTM): A Safe and Effective Topical Treatment for Head Lice (Pediculosis Humanus Capitis)

Abstract: Benzyl alcohol lotion 5% (BAL 5%) is a non-neurotoxic topical head lice treatment that is safe and effective in children as young as 6 months of age. The safety and efficacy of this pediculicide has been studied in 695 (confirm number) subjects in all phases of clinical development. Scanning electron micrographs (SEM) demonstrated that the active agent appears to stun the breathing spiracles open, enabling the vehicle to penetrate the respiratory mechanism (spiracles), therefore asphyxiating the lice. Initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 11 publications
0
58
0
4
Order By: Relevance
“…The most common adverse reactions after treatment included pruritus, erythema, pyoderma, and ocular irritation. Benzyl alcohol is available by prescription and is not ovicidal: package instructions state that it is to be applied topically for 10 minutes and repeated in 7 days, 40 although as with other nonovicidal products, consideration should be given to retreating in 9 days or using 3 treatment cycles (days 0, 7, and 13-15), as mentioned previously.…”
Section: Benzyl Alcohol 5%mentioning
confidence: 99%
“…The most common adverse reactions after treatment included pruritus, erythema, pyoderma, and ocular irritation. Benzyl alcohol is available by prescription and is not ovicidal: package instructions state that it is to be applied topically for 10 minutes and repeated in 7 days, 40 although as with other nonovicidal products, consideration should be given to retreating in 9 days or using 3 treatment cycles (days 0, 7, and 13-15), as mentioned previously.…”
Section: Benzyl Alcohol 5%mentioning
confidence: 99%
“…[91] Benzyl alcohol 5% lotion Physical First FDA-approved non-neurotoxic lice treatment, safe and effective in children as young as 6 months, not contraindicated in pregnancy, not ovicidal, applied for 10 minutes and repeated in 7 days, resistance unlikely as it works by asphyxiating lice. [92] Dimeticone 4% lotion Physical Made from high molecular weight dimeticone in cyclomethicone base, 4 randomized controlled trials have shown its high efficacy. [93][94][95][96] 15-minute application also effective.…”
Section: Ivermectin (Vs Malathion)mentioning
confidence: 99%
“…[86] Treatment Increasing resistance and adverse effects have raised concerns about head lice treatments, [87] encouraging search for new treatments [ Table 4]. [88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] No available pediculicide is 100% ovicidal, and resistance to lindane, pyrethrins, permethrin, and malathion has been reported. [100] Nits persist after the treatment and may be mistaken for active infestation [ Figure 5].…”
Section: Pediculosismentioning
confidence: 99%
“…A Ivermectina oral é um método químico também eficaz no combate da pediculose, apresenta elevada toxicidade, impedindo sua ampla utilização. Destaca-se também que a resistência desenvolvida pelos parasitas aos medicamentos contribui para a continuidade da infestação, sendo um dos maiores problemas no controle e erradicação da pediculose (8) . Esta capacidade de resistir à ação de medicamentos é o resultado da exposição continuada dos piolhos a doses subletais, ou seja, que se encontram abaixo da necessária para matar 100% dos parasitas (9) .…”
Section: Introductionunclassified
“…Apesar de existirem no mercado medicamentos eficientes, vale também ressaltar que os métodos físicos, ou seja, a catação e a escovação com pente fino para eliminação dos piolhos são fundamentais no processo de tratamento, já que os antiparasitários não combatem as lêndeas, mas somente o parasita adulto (3,8) . Atualmente não há nenhuma terapia que garante 100% de mortalidade dos ovos, daí a importância de realizar um tratamento manual eficaz na remoção de lêndeas.…”
Section: Introductionunclassified